Ambiguitas Kebijakan Dalam Pengelolaan Tambang Batu Gamping Di Kabupaten Buton Tengah: Antara Legalitas Formal Dan Legitimitas Sosial - Buradin Buradin; Zainul Abidin; Rahmawati Rahmawati (UNIVED PRESS, Universitas Dehasen Bengkulu, 2026)
This study analyses the nature and extent of policy ambiguity in the management of limestone mining in Central Buton Regency, Southeast Sulawesi. Employing a qualitative approach using a descriptive-explanatory case study method, data were collected through in-depth interviews, field observations and document analysis. The findings indicate that policy ambiguity is at a high level. The lack of clarity regarding objectives is reflected in the tension between regional fiscal targets and environmental protection. Ambiguity regarding means is evident in the absence of integrated standard operating procedures (SOPs) for production oversight and environmental impact verification. The fragmentation of authority between the central, provincial, and regency governments creates regulatory overlap, whilst the social legitimacy of the policy is weak due to the absence of meaningful public participation mechanisms. This study concludes that high levels of ambiguity render mining policy vulnerable to implementation distortions and social conflict. A reformulation of policy is required, emphasising clarity of indicators, strengthening coordination across levels of government, and integration between the Regional Spatial Plan (RTRW) and the mining licensing system.